(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
A mid-span deflection of concrete beam strengthened by FRP bars has been anticipated. A case of simply supported beam loaded by two point loads has been simulated by using artificial neural networks (ANNs) which are involved in MATLAB package, version 9.0.0.341360 (R2016a). The proposed model presupposes 60 beam specimens to collect the required data for the neural pattern. A set of 8 input variables was selected to construct the proposed neural pattern; these are, beam dimensions, concrete specifications, and FRP properties. While the mid-span deflection at the ultimate load, will be the output inconstant. The use of 9 nodes in the hidden layer is active in predicting the mid-span deflection. A comparison between the gained results and the past experimental data shows that the proposed neural pattern gives a reasonable anticipation with an overall error of 8.2 %.